Development of sustainable tourism in the case of nature park Karwendel, Austria - Gradinac Oliver; Jegdić Vaso (University Educons, Faculty of Sports and Tourism, Novi Sad, 2016)
The concept of sustainable tourism development is set so as to satisfy the present needs of tourists, so that their impact on nature is minimized, so that future generations can satisfy their travel needs in natural preserved areas. Sustainable development is the most complex concept that can be applied to tourism. Due to its complexity, it is not possible to determine precisely the definition of sustainable development, but it can be understood as a continuous process of achieving a balanced economic, environmental and social objectives. Likewise, sustainable tourism is a goal we should strive constantly. Tourism in protected areas should be organized so as to reveal their hidden values to visitors, and that doing so does not violate the peace and harmony of the ecosystem, monuments of material culture and way of life of local communities. The aim of this study is to contribute, through experience in sustainable development of tourism in the nature park Karwendel, to establishing of a model of development of tourism in protected areas with the participation of all stakeholders. The model of ecotourism development should lead tobalance of all components of the tourism product (attractive resources, infrastructure, equipment, organization, activities and experiences). We used an analytical and synthetic methods, qualitative case study, and missing data were collected through interviews.